Analisis Rekrutmen Karyawan Outsourcing Dengan Metode Analytical Hierarchy Process (AHP) Di CV Rama Jaya - Elly Setiadewi; Imas Widowati; Sis, Sis IV (Sekolah Tinggi Teknologi Wastukancana, 2024)
Recruitment is one of the human resource management activities to search for prospective employees who will occupy certain positions in an organization (agency). The implementation of recruitment must be able to run according to plan and be objective. Because, this recruitment process will have an impact on the company in the future. In this case, an analysis of outsourcing employee recruitment was carried out using the Analytical Hierarchy Process (AHP) method by determining the criteria and alternatives to be used. Data processing was carried out by manual calculations using Microsoft Excel and using Super Decision to ensure more precise processing results. The results of the study showed that the priority of criteria and alternatives in manual calculations and with super decision obtained the same results. So that decision making can be taken based on the results of data processing that has been carried out.